Real time quantification of low temperature radiofrequency ablation lesion size using phased array intracardiac echocardiography in the canine model: comparison of two dimensional images with pathological lesion characteristics. Issue 8 (14th July 2003) - Doi, A; Takagi, M; Toda, I; Teragaki, M; Yoshiyama, M; Takeuchi, K; Yoshikawa, J
Abstract : Objective: To evaluate the feasibility of quantifying low temperature radiofrequency catheter ablation (RFCA) lesions using a phased array intracardiac echocardiography (ICE) catheter—with better tissue penetration and in a deflectable device—in the canine model. Intervention: Low temperature radiofrequency (RF) energy (50–60°C at up to 40 W) was delivered to the left ventricle in 11 beagles for 60 seconds, using an 8 French catheter with a deflectable tip and a 4 mm distal electrode. Main outcome measures: Comparison of the width and depth of RFCA lesions measured by ICE with pathological findings. Results: 33 RF energies were delivered in 11 dogs. 31 lesions (94%) were confirmed at necropsy. 27 of 31 ablation lesions (87%) were detected by ICE. The mean (SD) width and depth of the ICE detected lesions were 10.4 (2.6) mm and 5.7 (1.9) mm, respectively. Pathological findings showed that RFCA lesions consisted of inner and outer layers. Macroscopically, the mean (SD) width and depth of the inner layers were 7.6 (2.3) mm and 3.6 (1.2) mm and those for the whole layers were 10.0 (2.8) mm and 5.3 (1.5) mm, respectively. Microscopically, the inner and outer layers corresponded to necrotic and oedematous areas, respectively. The ICE detected lesion size had better correlation with the pathological measurements of the whole layers in width ( r = 0.911) and in depth ( r = 0.756). Conclusion: The real time evaluation of RFCA lesion size using the phased array ICE is feasible, even with a low temperature RF application. However, ICE slightly overestimates RFCA lesion size compared with pathological necrotic lesion size.